Comparison of Postoperative Stress Urinary Incontinence between Anteroposterior Dissection and Modified Gilling Method in Holmium Laser Enucleation of the Prostate. - Shishido, Toshihide; Hirasawa, Yosuke; Kashima, Takeshi; Hashimoto, Takeshi; Satake, Naoya; Hayashi, Kenjiro; Aizawa, Taku; Harada, Kazuharu; Taguri, Masataka; Ohno, Yoshio (Urology Journal, 2024)
Purpose: Few studies have evaluated the usefulness of anteroposterior dissection holmium laser enucleation of the prostate (HoLEP). Thus, this study investigated the incidence of stress urinary incontinence (SUI) after HoLEP and usefulness of anteroposterior dissection HoLEP in preventing postoperative SUI. Materials and Methods: In total, 288 patients who underwent HoLEP performed by a single experienced surgeon between May 2014 and September 2021 were enrolled. Furthermore, 134 patients underwent retrograde dissection using the modified Gilling method (surgery 1) and 154 patients underwent anteroposterior dissection HoLEP (surgery 2). The risk factors for SUI, as well as the rates of SUI improvement for the two surgical procedures, were evaluated. Results: Postoperative SUI was observed in 58 (20.1%) of 288 patients, of whom, 48 (82.8%) recovered continence within 6 months. Ten patients (17.2%) required more than 6 months to recover continence. SUI incidence 1 month after HoLEP was 29.9% (40/134 patients) for surgery 1 and 11.7% (18/154 patients) for surgery 2; a statistically significant difference was observed between the two groups (odds ratio [OR], 0.311; 95% confidence interval [CI], 0.168–0.575; p < 0.001). In addition, surgery 2 was significantly associated with early recovery from SUI compared with surgery 1 (stratified hazard ratio, 0.782; 95% CI, 0.615–0.995; p < 0.001). The multivariable analysis demonstrated that only surgical procedure (OR, 0.350; 95%CI, 0.168–0.732; p=0.005) was an independent predictor of SUI. Conclusion: We reaffirmed that anteroposterior dissection HoLEP is a useful procedure for reducing the risk of postoperative SUI and early recovery of urinary continence.